Kedudukan Perempuan dalam Hukum Waris Masyarakat Adat Karo - Saragih, Rayani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to determine and analyze the position of women in the inheritance law of the Karo indigenous people. The research method used in this research is normative juridical research by conducting literature studies and field studies by conducting interviews with traditional stakeholders in Karo Regency. The result of this research is that the position of women in the inheritance law of the Karo community has its own rules. Karo customary inheritance rights are contained in the provisions of the MA-RI Jurisprudence No. 179/K/SIP/1961 which stipulates that the equal rights of men and women have created pros and cons among the Karo adat community. The position of women in the kinship system in Lingga Village is twofold, namely the position as a child and the position as a wife. The position as children is that girls are not the next generation of the family because they are considered temporary, this is because at one time the position of women in Karo customary inheritance rights is carried out in several ways, including giving affection (Pemere Keleng Ate), the rule of law concerning inheritance (Peradaten Kerna). Erta Tading-Tadingen) and provide educational facilities. The form of property given is in the form of trinkets and land/rice fields.